Pengaruh Leader Member Exchange (LMX) dan Karakteristik Pekerjaan Terhadap Kinerja dengan Kepuasan Kerja Sebagai Variabel Mediasi Studi pada Personil Sub Bagian Umum Akademi Kepolisian Semarang - Wahyu Teguh Prasetyo; Endang Tjahjaningsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of the research is to analyze the influence of leader member exchange and job characteristics on performance mediated by job satisfaction in the General Subdivision Personnel of the Semarang Police Academy. The population used in this research was personnel serving in the General Sub-Section of the Semarang Police Academy, totaling 140 people. The sampling method in this research used a census. The data analysis technique uses regression using the SPSS program and the Sobel test. The results of this research can be concluded that LMX has a positive and significant effect on job satisfaction. Job characteristics have a positive and significant effect on satisfaction. LMX has no effect on personnel performance. Job characteristics have a positive and significant effect on performance. Satisfaction has a positive and significant effect on performance. Based on the results of the Sobel test, it is proven that job satisfaction mediates the influence of LMX on performance. Likewise, job satisfaction mediates the influence of job characteristics on performance.